2017
DOI: 10.21037/jovs.2017.03.23
|View full text |Cite
|
Sign up to set email alerts
|

The role of wet lab in thoracic surgery

Abstract: During the last three decades, minimally invasive surgery has become common practice in all kinds of surgical disciplines and, in Thoracic Surgery, the minimally invasive approach is recommended as the treatment of choice for early-stage non-small cell lung cancer. Nevertheless, all over the world a large number of lobectomies is still performed by conventional open thoracotomy and not as video-assisted thoracic surgery (VATS), which shows the need of a proper training for this technique. Development and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…As a solution to this problem, it has been reported that the creation of video-assisted thoracoscopic lobectomy simulators and training programs, the use of dry or wet labs, and the introduction of virtual-reality technology into these programs are useful in educating thoracic resident doctors. [19][20][21][22][23] In this study, the thoracic resident doctor trained in dry and wet labs before the first surgery. He trained in suturing using models and folding birds with origami paper in the dry lab.…”
Section: Discussionmentioning
confidence: 99%
“…As a solution to this problem, it has been reported that the creation of video-assisted thoracoscopic lobectomy simulators and training programs, the use of dry or wet labs, and the introduction of virtual-reality technology into these programs are useful in educating thoracic resident doctors. [19][20][21][22][23] In this study, the thoracic resident doctor trained in dry and wet labs before the first surgery. He trained in suturing using models and folding birds with origami paper in the dry lab.…”
Section: Discussionmentioning
confidence: 99%
“…Wet and dry labs provide another step on the learning process because they add to the training scenario the tissues and anatomical relationships between structures (22). Live animals provide excellent training scenarios, although the availability is limited, and there is no opportunity for repetition training as in a simulator, where a trainee is free to perform around 10 procedures in a single training session.…”
Section: Teaching Goals and Methodsmentioning
confidence: 99%
“…Dry and wet lab exercises were also found to be useful in VATS training (14). Left sided VATS resections are performed in live pigs.…”
Section: Incorporation Of Numbers and Other Training Toolsmentioning
confidence: 97%